Epidemiologia e danos causados pela meleira do mamoeiro no estado da Bahia e diversidade genética do papaya meleira virus 2 (pmev2) - Cruz Neto, Alírio José da (2020)
Bahia stands out among the largest papaya producing states in Brazil. Among the factors limiting the culture, the Papaya sticky disease, or “meleira” stands out. Honeydew is caused by the Papaya meleira virus (PMeV). Later, in plants with symptoms, a second virus was identified: Papaya meleira virus 2 (PMeV2). Thus, the disease has been called the PMeV Complex. In this sense, the objectives of this study were to identify risk factors for papaya honey in conditions in the extreme south of the state of Bahia; determine the spatio-temporal pattern of the disease in the region's cultivation conditions; characterize the genome of a PMeV2 isolate; to estimate the genetic diversity and phylogenetic relationships between PMeV2 isolates from orchards in northeastern Brazil and to know the damage caused by papaya in conventional cultivation of papaya in the extreme south of Bahia. Risk analyzes have shown that there is more risk that a mixed orchard may have meleira. Aggregation of diseased plants was observed in less than half of the evaluated areas. The analysis of isopathic areas indicated a tendency for epidemics to start from the edges of the orchards. However, there was no evidence of a higher incidence of honeydew at the edges of the orchards as the epidemics progressed, which suggests the occurrence of secondary outbreaks. The sequence obtained in this work, called PMeV2-RN, has 4,435 nucleotides and has about 94% identity with the isolate PMeV2-ES from Espírito Santo. The sequence contains two ORFs predicted at different reading stages, the first encoding a 238 amino acid polypeptide that has 88% identity with the corresponding PMeV2-ES protein, and the second encoding a 473 amino acid protein, which has 100% identity with the PMeV2-ES RdRp protein. Phylogenetic analyzes showed greater proximity between the isolate PMeV2-ES and the isolates PpVQ and PMeV-Mx than with PMeV2-RN, which seems to belong to a distinct strain of this virus. The analysis of the nucleotide sequences of the isolates from different papaya producing regions in Brazil indicated a high degree of similarity between the isolates, which did not form geographically structured groups. Considering the survey of the average prices paid to the producer, the profitability indicators for papaya Havaí and Formosa are recommended up to 40% of losses for meleira.